Intravascular epithelioid haemangioma mimicking eosinophilic granulomatosis with polyangiitis: a rare diagnostic dilemma - Athira Warrier; Kevin Loudon; Victoria Bardsley (Clinical Medicine)
Introduction: Distinguishing between benign and inflammatory vascular disorders can be challenging, especially when clinical and laboratory findings overlap. Epithelioid haemangioma (EH), also known as angiolymphoid hyperplasia with eosinophilia, is a rare, benign vascular tumour that predominantly affects the head and neck, often involving the skin and small vessels.1 One such diagnostic challenge arises in differentiating EH from eosinophilic granulomatosis with polyangiitis (EGPA), a rare but life-threatening small- to medium-vessel vasculitis. EGPA typically presents with asthma, sinusitis and systemic eosinophilia, and, similar to EH, can show prominent eosinophilic infiltration.2 Given these similarities, misinterpreting EH as EGPA could lead to unnecessary and potentially harmful immunosuppressive therapy. Methods: A detailed review of the patient's clinical records was conducted with consent, followed by an extensive literature review on EH, eosinophilic dermato-vasculitides and eosinophilic vasculitides. Discussion: We present the case of a 44-year-old White man with a history of well-controlled asthma, eczema and recurrent sinusitis who presented with a tender swelling over the left temple. He was noted to be hypertensive, and his tests showed peripheral eosinophilia of 0.62 × 109/L, with weak p-ANCA and ANA positivity. Inflammatory markers (ESR and CRP) were within normal limits. Doppler ultrasound identified a pseudoaneurysm of the temporal artery (Fig 1). Given his background of asthma and sinusitis, EGPA was a key differential, while giant cell arteritis (GCA) was also considered because of temporal artery involvement. The affected segment of the temporal artery was completely excised to manage the pseudoaneurysm and obtain tissue for histological analysis (Fig 2).Histology revealed eosinophilic vasculitis with extensive destruction of the internal elastic lamina and prominent eosinophilic infiltrates, raising suspicion for EGPA or EH. However, granulomas were notably absent. Comprehensive systemic evaluation, including urine studies, computed tomography (CT) aorta, positron emission tomography (PET)-CT and serologic testing, showed no evidence of additional systemic involvement or parasitic causes of eosinophilia.A second opinion was sought from a specialist dermatopathology lab. The biopsy demonstrated a predominantly eosinophilic inflammatory infiltration within the arterial wall, along with an organised thrombus in the lumen. Notably, vascular channels lined by plump epithelioid endothelial cells with pink cytoplasm, vesicular nuclei and a single nucleolus were observed. Immunohistochemistry confirmed the presence of epithelioid endothelial cells positive for CD31 and ERG. This ‘hob-nailed’ appearance, characteristic of EH, was consistent with a rare predominantly intravascular EH with minimal extravascular involvement.3–5 Given that EH is a benign condition treated surgically,5 no further intervention was required. At a 12-month follow-up, the patient remained asymptomatic, and eosinophilia had resolved. Conclusion: Purely intravascular epithelioid haemangioma is a rare entity, with only a limited number of cases reported in the literature to date.6,7 This case posed a unique diagnostic challenge given the juxtaposition of several clinical features of EGPA. The key to diagnosis was in the histology, which revealed the absence of the palisading granulomas of EGPA8 and the ‘hobnailed’ appearance of EH. Accurate diagnosis is critical to avoid unnecessary immunosuppression, which would otherwise be initiated in EGPA management.8